Individual Differences in Intention to Fake Job Interviews: Personality, Self-Monitoring, and the Theory of Planned Behaviour. (2015) - Lester, Candice; Anglim, Jeromy; Fullarton, Christie
Abstract : When job applicants lie in job interviews, they can deprive a more honest candidate of a job and deprive an organisation of the best employees. To better understand job interview faking, the present study examined the effect of general dispositions and domain-specific beliefs on the intention to fake job interviews. A community sample of 313 participants completed measures of personality (i.e., extraversion, neuroticism, conscientiousness) and self-monitoring, and a domain-specific measure of beliefs about faking job interviews based on the theory of planned behaviour, which measured attitudes, subjective norms, and perceived behavioural control. Results indicated that the measure of attitudes was the strongest predictor of intention to fake. In line with the compatibility principle, the domain-specific measures based on the theory of planned behaviour correlated much more strongly with intentions to fake job interviews than did the general measures of personality or self-monitoring. Of the dispositional measures, lower conscientiousness, higher neuroticism, and higher self-monitoring was associated with greater intention to fake job interviews. The findings support a model whereby the effect of personality on intentions is partially mediated by domain-specific beliefs.